Pressure-volume analysis reveals characteristic sex-related differences in cardiac function in a rat model of aortic banding-induced myocardial hypertrophy: research article - Ruppert, Mihály; Korkmaz-İçöz, Sevil; Loganathan, Sivakkanan; Lehmann, Lorenz; Karck, Matthias; Szabó, Gábor (American journal of physiology. Heart and circulatory physiology, 2018)
Sex differences in pressure overload (PO)-induced left ventricular (LV) myocardial hypertrophy (LVH) have been intensely investigated. Nevertheless, sex-related disparities of LV hemodynamics in LVH were not examined in detail. Therefore, we aimed to provide a detailed characterization of distinct aspects of LV function in male and female rats during different stages of LVH. Banding of the abdominal aorta (AB) was performed to induce PO for 6 or 12 wk in male and female rats. Control animals underwent sham operation. The development of LVH was followed by serial echocardiography. Cardiac function was assessed by pressure-volume analysis. Cardiomyocyte hypertrophy and fibrosis were evaluated by histology. At week 6, increased LV mass index, heart weight-to-tibial length, cardiomyocyte diameter, concentric LV geometry, and moderate interstitial fibrosis were detected in both male and female AB rats, indicating the development of an early stage of LVH. Functionally, at this time, impaired active relaxation, increased contractility, and preserved ventricular-arterial coupling were observed in the AB groups in both sexes. In contrast, at week 12, progressive deterioration of LVH-associated structural and functional alterations occurred in male but not female animals with sustained PO. Accordingly, at this later stage, LVH was associated with eccentric remodeling, exacerbated fibrosis, and increased chamber stiffness in male AB rats. Furthermore, augmented contractility declined in male but not female AB animals, resulting in contractility-afterload mismatch. Maintained contractility augmentation, preserved ventricular-arterial coupling, and better myocardial compliance in female rats contribute to sex differences in LV function during the progression of PO-induced LVH.NEW & NOTEWORTHY We investigated sex differences in pressure overload-induced left ventricular myocardial hypertrophy for the first time on the functional level by pressure-volume analysis. We found that left ventricular hypertrophy was initially characterized by prolonged active relaxation, increased contractility, and maintained ventricular-arterial coupling in both sexes. However, at a later stage, augmented contractility declined in mate but not female rats, resulting in contractility-afterload mismatch. Furthermore, in male rats, increased myocardial stiffness also contributed to hypertrophy-associated diastolic dysfunction.
Gesehen am 03.05.2018